Devolopment of temporary joining elements in lightweight metal systems between complexity of form and simplicity of installation (Analytical study) - Hany Fawzy Abu Elazam; Ahmed Hamed Mostafa (Maǧallaẗ Al-Turāṯ wa Al-Taṣmīm, 2021)
Complexity and simplicity are two interrelated terms that refer to each other in many fields of knowledge. Complexity is an integrative structural arrangement that indicates the number of possibilities in a system. In design, complexity is a case that stems from dimensions and philosophical visions of different design trends. Complexity is usually employed to change the stereotypes of systems and products to interest the end user. Simplicity means that something is easy to understand or do and it is a way of describing seemingly complex results using just a few rules, bits, and interactions. The structural assembly of metall systems includes many single elements that are grouped temporarily together, each of them has a secondary function that shares together to achieve the overall function of the required system. The multiplicity of parts and components of the system may result in varying degrees of structural and functional complexity, the degree of which varies according to the function of the system, its environment and the characteristics of its components. As long as the end user becomes a part of the system building process, it is important that complexity is not reflected in the end user and the process of assembling system is simplified with the least amount of skill.